VITAMIN A STATUS AND THE EFFECT OF ORAL SUPPLEMENTATION IN PREGNANT NIGERIAN WOMEN (1991)
This study was designed to investigate vitamin A nutritional status of pregnant and non pregnant non lactating Nigerian women. The beneficial effects of oral vitamin A supplementation was also investigated in the pregnant women. The study was carried out in three one was the cross-sectional study carried out on 22, 88 and 61 pregnant women in the 1st, 2nd and 3rd trimesters. The controls were 35 non pregnant non lactating women in the proliferative phase of the menstrual cycle. Their ages ranged from 18 to 45yrs with a mean age of 27.8+/— 6.82yrs. The subjects were randomly selected from both the University teaching and Adeoyo hospitals, Ibadan and the study lasted for a period of nine months. The result of the study showed that 11% of the subjects had plasma vitamin A levels in the deficient range << 20ug/dl) while 60% had marginal values (20 - 29ug/dl). Plasma vitamin A levels was observed to decrease as pregnancy progressed <P<0.05). The levels of B—carotene were however observed to be in the normal range. The second phase of the study was designed to determine the adequacy of vitamin A in the body using the relative dose response test (RDRT) technique. Thirty pregnant women at different trimesters of pregnancy and ten non pregnant non lactating women were studied for a period of five weeks. 13.6% of the subjects had RDRT values greater than 20% which is indicative of liver store less than 20ug/g. This level is associated with deficiency of vitamin A. The longitudinal study was the third phase of the study. This phase spanned a period of 18months. Twenty eight pregnant women were supplemented with either oral vitamin A or lactase in gelatin capsule (placebo) from the 14th week of pregnancy until 6weeks postpartum. Vitamin A supplementation maintained the packed cell volume (PCV), increased both the plasma vitamin A and retinal binding protein (RBP) levels in the vitamin A supplemented subjects. Though the neonates of mothers supplemented with vitamin A had higher higher birth weights, plasma and retinol binding protein levels when compared with the controls, the difference was however not significant. The levels of the plasma proteins were observed to decrease significantly during labour and immediately postpartum. Proximate analysis of the meals (as consumed) of the pregnant mothers in the longitudinal study revealed that the pregnant women in this environment met only 47% of their daily requirement for Vitamin A.